Procesamiento Digital de Señales Sísmicas con Matlab - Jiménez Tintaya, César Omar (2007)
The purpose of this work is to implement an algorithm to identify the seismic waves parameters: P phase, S phase, amplitude, period and duration. For this, digital signal processing and the programming language Matlab will be applied to perform the automatic reading of seismic signal parameters. As mathematical tools, the discrete Fourier transform (fft) to study the frecuency components of the signal and the Hilbert transform to obtain the envelope signal, will be used. A graphical user interface in Matlab was designed and implemented for reading (with functions of automatic reading or manual reading) seismic signals with three components. In this way, it makes easy the routine of reading the seismic signals within a great set. The results of the automatic algorithm agree with that of a manual operator for a great Signal/Noise ratio.